Association of Inflammatory Markers and Dietary Patterns with Components of Metabolic Syndrome in Working Women (Medical Forum Monthly, 2024)
Objective: The main objective of the study is to find the association of inflammatory markers and dietary patterns with components of metabolic syndrome in working women.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Physiology, Liaquat University of Medical and Health Sciences Jamshoro from January 2023 to December 2023.Methods: A total of 384 female aged between 18 to 50 years were included in the study. Data were collected through a systematically designed questionnaire. Inflammatory blood markers were the main focus of the study following the participants’ fasting (overnight), and they were measured.Results: Data was collected from 384 female participants according to inclusion and exclusion criteria. Mean age of the participants was 39.08±10.41 years. Among the participants, 22.4% reported current pregnancy, highlighting the diversity in reproductive stages, while 45.8% were identified as menopausal. The average BMI of 29.12 and prevalence of abdominal adiposity at 30.5% suggest a need for targeted interventions in women's health. Inflammatory biomarkers show significant associations with various health-related variables. Individuals with higher BMI categories exhibited elevated levels of C-reactive protein (CRP), with mean values of 3.0 ± 1.5 in the normal BMI range (18.5-24.9), 4.5 ± 2.0 in the overweight category (25-29.9), and 6.2 ± 2.8 in the obese group (≥30) (p < 0.001). Work duration also played a role in influencing erythrocyte sedimentation rate (ESR), as individuals with longer work durations (>10 years) displayed higher mean ESR levels (20.0 ± 10.0) compared to those with shorter durations (<5 years and 5-10 years) (p < 0.001).Conclusion: It is concluded that there is an association between inflammatory markers, dietary patterns, physical activity, and components of metabolic syndrome in working women. Emphasizing lifestyle modifications, including healthier dietary choices and increased physical activity, holds promise in mitigating metabolic syndrome risk factors in this population, although further research is needed to elucidate causative mechanisms and refine targeted interventions.